Improving Science Literacy Skills through Interactive Physics E-Learning for students at Lapandewa High School - Boma, Muslimin; Mahmudah, Rida Siti Nur'aini; Salam, Salam; Pratiwi, Ika; Syahrir, Syahrir; Chen, Diki; Nofianti, Nofianti; Ariatami, Rezky Nur (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study aims to develop physics e-learning to improve students' science literacy skills at SMAN 3 Lapandewa. This research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis stage involves conducting observations and in-depth interviews at school; the design stage involves designing the initial e-learning product; and the development stage involves developing the e-learning product. The implementation stage involves implementing the developed product, while the final stage involves evaluating the product and its impact on learning outcomes. The determination of research samples involves the use of random sampling techniques and a specific research design. Pretest-Posttest Control Group Design. The research sample amounted to 25 respondents in the control class and 29 respondents in the experimental class. Three validators declared the analysis of science literacy-based teaching materials on temperature and heat feasible, citing easy-to-understand criteria with an average readability of 74.11%. The increase in science literacy skills of students who use science literacy-based teaching materials is higher than that of students who use teaching materials used at school. The increase in science literacy skills among students who use science literacy-based teaching materials is 0.63, compared to 0.38 for students who use traditional school books. Therefore, we can conclude that e-learning enhances students' science literacy abilities.